Menakar Prospek Kelayakan Investasi Industri Peralatan Rumah Tangga Berbahan Baku Aluminium - Ignatia Martha Hendrati; Nuruni Ika KW; Sishadiyati Sishadiyati (Universitas 17 Agustus 1945 Surabaya, 2014)
Abstract: East Java Province has the potential to develop the business housewares made from aluminum. Industry is very promising and has good prospects. Demand for refined products result from this in the form of aluminum household appliances market is very attractive both in neneri market and overseas market. For overseas market demand of houseware products made from aluminum are from Japan, India, the Netherlands and China.Potential industry of household appliances are made of aluminum in East Java feasible to be developed. Based on household demand akanperalatan higher, both in local and international markets. Demand for household appliances for the local market is currently very high but still a small portion of raw materials imported from china. As a result, prices tend to rise.Key words: Aluminum, Industrial Appliances, Business Feasibility.